How Do Populist Radical Right Parties Differentiate their Appeal? Evidence from the Media Strategy of the Hungarian Jobbik Party. Issue 1 (3rd January 2023) - Borbáth, Endre; Gessler, Theresa
Abstract: As they become more successful, populist radical right parties face a tension between keeping their nativist credentials and moderating their appeal to gain new voters. We argue that differentiating party messages to core supporters and the wider electorate allows parties to pursue both goals. We outline and empirically illustrate the previously underexplored phenomenon of selective messaging based on the communication strategy of the Hungarian Jobbik party throughout its lifespan (2006–19) in partisan outlets, press releases and Facebook. Using a dictionary approach, we map the co-evolution of populist and nativist mobilization under conditions of supply- and demand-side changes. Our results show the decline and transformation of Jobbik's nativist appeal, and an increasing reliance on populism. The trend is not uniform; Jobbik relies on nativism as a function of targeting party identifiers or the general electorate in specific media outlets. Our findings show the importance of mapping parties' programmatic appeal across platforms and over time.